Household Saving in Developing Countries - Inequality, Demographics and All That: How Different are Latin America and South East Asia? - Miguel Székely; Orazio P. Attanasio (Inter-American Development Bank, Research Department, 2000)
East Asia and Latin America have diverged in several dimensions in the past three decades. This paper compares household saving behavior in two countries in each region (Mexico, Peru, Thailand and Taiwan). We make four contributions. First, we provide the first comparisons of savings in these two regions at the micro level using synthetic cohort techniques. Second, rather than focusing only on total household saving, as is common in the literature, we disaggregate the population into education groups to determine whether there are differences in saving behavior along the distribution of income. Third, we construct forecasts of future aggregate household saving rates, based on demographic projections. Fourth, we provide evidence that allows for testing the relevance of the life cycle model for explaining the differences in saving behavior.
Keywords: 330; Sparen; Privater Haushalt; Bildungsniveau; Einkommensverteilung; Vergleich; Ostasien; Lateinamerika